A new approach to modeling and analysis portfolio investment solutions - Dobrina M., Endovitskiy D., Davnis V., (Opción, 2019)
The possibility of using an econometric model with a discrete dependent variable in the problems of forming portfolio decisions is investigated. On the basis of the Wiener regression, a diagonal portfolio investment model is constructed, the calculations of which made it possible to clarify the interpretation of the yield-risk relationship. As a result, the yield of each financial asset that is traded on the market depends on the investment potential of the market. In conclusion, the higher the risk, the greater the deviation of the expected level of profitability from the level guaranteed by the investment potential of the market.